HUBUNGAN OBESITAS DAN POLA AKTIVITAS DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS III DENPASAR UTARA: RELATIONSHIP OF OBESITY AND ACTIVITY PATTERNS WITH HYPERTENSION IN PUSKESMAS III NORTH DENPASAR WORK AREA - Damayanti, Sri; Oktaviani, Wiwik; Mirayanti, Ayu (Stikes Wira Medika Bali, 2020)
Hypertension is a condition which attacks productive age between 35 to 60 years old which is increasing from year to year. Hypertension is caused by two factors, there are controled factor and uncontrolled factor such as obesity and physical activity. High blood pressure cannot be healed but is can be controled by premier prevention and secondary prevention. The purpose of this study was to find out about the relationship between obesity and activity patterns with hypertension in the working area of Puskesmas III North Denpasar. The method used on this research is correctional descriptive with cross sectional approach by taking the non probability sampling and purposive samplic technic. The data analysis is using rank spearman test. The statistic test result obtained is r = 0,426 and p-value = 0.001 or p ≤ 0,05. The statistic test result obtained is r = -0,421 and p-value = 0.001 or p ≤ 0,05. Its means that there is a correlation of obesity and activity patterns with hypertension in the working area of puskesmas III denpasar utara, therefore it is expected that medical personnel, especially nursing, can improve health services, especially promotive and preventive programs and counseling about risk factors that can cause hypertension